Perceptual and instrumental analysis of hypernasality in children with repaired cleft palate - Henna Raunak Seth Tak; Aarti Pushkar Waknis; Sneha Prakash Kulkarni (Wolters Kluwer Medknow Publications, 2016)
Context: Hypernasality is a frequently encountered problem in the speech of individuals with cleft palate with/without cleft lip (CP ± L). Aims: The aim of the present study was to explore the relation between perceptual and instrumental analysis of hypernasality in children with repaired CP ± L. Settings and Design: Comparative. Subjects and Methods: Children were divided into two groups. Group I included of 30 children operated for CP ± L and Group II included children in the age group of 4 -11 years in the age range of 4-11 years were included in the study. Specially constructed oral sentences in Marathi were used for the perceptual and instrumental analysis of speech. In addition, a number counting task and picture description was recorded for perceptual assessment. Nasal view Dr. Speech "Version 4 was used for instrumental assessment. Perceptual assessment for hypernasality was carried out by listening to the prerecorded speech samples by two experienced speech language pathologists. Statistical Analysis Used: Kappa coefficient, Pearson's product moment correlation. Results: The results of the study indicated a strong relationship between perceptual rating of nasality and nasalance scores for oral sentences. Conclusions: Nasal view was able to distinguish between normal resonance and hypernasality in speech of children with CP ± L.